Roman helmets with a browband shaped as a vertical fronton - NEGIN, Andrei (Historia i Świat, 2015)
Roman propaganda monuments are known best of all and they are still often cited, especially in Hollywood blockbusters. Despite the many doubts expressed by modern researchers, they continue to be sources valuable in many aspects as those monuments, mostly located in the capital, show how military weapons were perceived by the inhabitants of the capital, including the sculptors who were working on these monuments. There are many images of so-called Attic helmets on Roman monuments dated back to the first two centuries AD. As a rule, all of them are richly decorated with embossed floral ornament, have a browband with volutes in the temporal region and equipped with longitudinal crests with gorgeous plumes. The question arises, what are the samples were depicted on the Roman reliefs? How accurately this specimen have been reproduced by artists and sculptors, or, perhaps, we see only a reflection of the Hellenistic artistic tradition? There are helmets with a browband shaped as a vertical fronton with volutes existed. Their later modification is presented by finds from Guisborough, Theilenhofen, Chalon-sur-Saône. The pieces of the Ist century AD – early IInd century AD are Weiler-type helmets with a decorated riveted browband. They are the helmets from Nijmegen, Brza Palanka and from other places. The pieces from Butzbach and Hallaton can be considered as a transitional design between early and later helmet modifications with a vertical fronton. Thus, all of the above finds suggest that Attic helmets with browbands, which are often depicted on Roman propaganda monuments, are not the sculptors’ invention, but helmets really common in the Roman imperial army, imitating the models of the earlier period.